2015
DOI: 10.1016/j.amjcard.2015.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Physical Activity and Incident Atrial Fibrillation (from the Multi-Ethnic Study of Atherosclerosis)

Abstract: Prior studies have raised the question of whether an association exists between physical activity and atrial fibrillation (AF). We used the Multi-Ethnic Study of Atherosclerosis (MESA) database to examine the association between physical activity and AF in a diverse population without clinically recognized cardiovascular disease (CVD). MESA participants (N=5793) with complete baseline physical activity and covariate data were included. Cox proportional hazards models were used to calculate hazard ratios (HR) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 22 publications
(24 reference statements)
0
48
0
Order By: Relevance
“…Data from the Multi-Ethnic Study of Atherosclerosis (MESA), concluded that higher levels of physical activity were associated with lower risks of atrial fibrillation. 15 Another important national study observed that the occurrence of in-hospital cardiovascular complication was associated to the time of physical inactivity regardless of age, systolic blood pressure and previous congestive heart failure. 16 The agglomeration of risk factors showed to be similar between men and women according to the study conducted in Brazilian capitals.…”
Section: Resultsmentioning
confidence: 99%
“…Data from the Multi-Ethnic Study of Atherosclerosis (MESA), concluded that higher levels of physical activity were associated with lower risks of atrial fibrillation. 15 Another important national study observed that the occurrence of in-hospital cardiovascular complication was associated to the time of physical inactivity regardless of age, systolic blood pressure and previous congestive heart failure. 16 The agglomeration of risk factors showed to be similar between men and women according to the study conducted in Brazilian capitals.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 19 studies were included in this review which included 2 post-hoc analysis of randomized controlled trials, [10,12] 10 cohort studies [8,11,16,17,[21][22][23][26][27][28]] and 7 casecontrol studies [7,9,[29][30][31][32][33] with 511,503 participants. The process of study selection is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…[10][11][12]16,[21][22][23][24][25][26][27][28] which could be pooled in meta-analysis these studies showed a borderline significant increase in AF(RR1.98 95%CI 1.00-3.94, I 2 =59%,) ( Figure 4). [7][8][9]29,32,33] Two case-control studies evaluated the approximate hours of physical activity and the study by Calvo et al [30] reported significant increases in AF with more cumulative heavy sports activity (>2000h OR 4.25 95% CI 11.34, 172 participants) while other study by Elosua et al [7] evaluating sports practice found no significant difference with any hours of sports activity.…”
Section: Studies Of Physical Activity In General Populationmentioning
confidence: 99%
“…75 In the MESA cohort, no association was found between vigorous physical activity or total intentional exercise and incident AF, but in a subgroup of patients who reported no vigorous activity, total intentional exercise was associated with a lower AF incidence. 76 When organized in the form of exercise program tailored for age and physical ability, as was done in the CARDIO-FIT study (Impact of Cardiorespiratory Fitness on Arrhythmia Recurrence in Obese Individuals With Atrial Fibrillation), patients who achieved higher cardiorespiratory fitness were less likely to develop recurrent AF, although low cardiorespiratory fitness was an independent predictor of AF recurrence (HR, 2.75; 95% CI, 1.61-4.68). 77 Physical activity not only improved rhythm control but also reduced rates of cardiovascular death, all-cause mortality, and thromboembolic events.…”
Section: Impact Of Physical Activity and Obesitymentioning
confidence: 99%